Marka Finansmanı - (:unkn) unknown (My University, 2002)
0

A brand is simply a product or service, which can be distinguished from its competitors. Successful brands are those meet the needs and aspirations of a defined target market. Financial markets increasingly recognize that intangible rather than tangible assets are the primary source for corporate value. Tangible product features can be rapidly copied. Intangible features cannot. They create emotional barriers to competition and sustainable, long-term advantage. Most tangible assets have finite lives. But brands, if well managed, can be timeless. Brands have the power to influence consumer demand, trade distribution, staff loyalty, supplier terms and investor sentiment, transforming business performance and financial returns. But while corporate assets may be increasingly "intangible" their performance needs to be rigorously measured. Financial accountability is paramount and return on brand investment is becoming a critical issue for the board and finance director. Brand finance specializes in understanding, measuring, managing and exploiting Brands. The aim of this study is to explain Brand Equity, Brand Valuation, Brand Strategy that are the elements of Brand Measurement.